Overview of Nickel Oxide (NiO) Thin Films for Gas Sensing Applications - Sunil Rameshgir Gosavi; H.S. Gawale; K. R. Sali (New Trends in Physical Science Research Vol. 5, 2022)
Recently, the issue of environmental pollution is becoming serious problem due to emission of various toxic gases from the daily activities in our life. These issues have inspired many researchers to create and fabricate cost-effective high performance gas sensors which can detect toxic gases and monitor its emission so as to protect the environment and human health. Nickel oxide (NiO) is one of the important metal oxide semiconducting materials which can be investigated as potential gas sensing material. In this chapter, we focus on the overview of the different methods used for the synthesis of NiO thin films and spray pyrolysis method towards NiO thin films synthesis. Moreover, we discuss the influence of film thickness on the crystallinity and functional properties of as-deposited NiO thin films. This chapter discusses the gas sensing measurements using NiO thin films synthesized at optimized nickel (Ni) concentration.